Symptomatic Cryptococcal Meningitis with Negative Serum and Cerebrospinal Fluid Cryptococcal Antigen Tests - Nanfuka V (Dove Medical Press, 2021)
Vivien Nanfuka,1,* Mkhoi L Mkhoi,2– 4,* Jane Gakuru,2 Richard Kwizera,2 Joseph Baruch Baluku,5 Felix Bongomin,6,7 David B Meya1,2,6 1Infectious Diseases Unit, Kiruddu National Referral Hospital, Kampala, Uganda; 2Infectious Diseases Institute, College of Health Sciences, Makerere University, Kampala, Uganda; 3Mark Wainberg Fellowship Programme, Infectious Diseases Institute, College of Health Sciences, Makerere University, Kampala, Uganda; 4Department of Microbiology and Parasitology, College of Health Sciences, University of Dodoma, Dodoma, Tanzania; 5Division of Pulmonology, Kiruddu National Referral Hospital, Kampala, Uganda; 6Department of Medicine, School of Medicine, College of Health Sciences, Makerere University, Kampala, Uganda; 7Department of Medical Microbiology, Faculty of Medicine, Gulu University, Gulu, Uganda*These authors contributed equally to this workCorrespondence: Felix BongominDepartment of Medical Microbiology, Faculty of Medicine, Gulu University, Gulu, UgandaTel +256-784-523-395Email drbongomin@gmail.comBackground: Cryptococcal meningitis is a leading cause of mortality in advanced HIV disease. A positive cerebrospinal fluid cryptococcal antigen (CrAg) test defines cryptococcal meningitis. Herein, we present a patient with serum and cerebrospinal fluid CrAg negative cryptococcal meningitis, despite a positive cerebrospinal fluid India ink examination and quantitative culture.Case Details: A 56-year-old HIV-positive Ugandan woman, with an undetectable HIV RNA viral load and CD4+ T-cell count of 766 cells per microlitre presented with signs and symptoms consistent with cryptococcal meningitis. Her serum and cerebrospinal fluid CrAg tests were negative despite having a positive cerebrospinal fluid India ink and quantitative culture. On day 1, she was commenced on intravenous amphotericin B deoxycholate (1mg/kg) for 3 days (considering 10 CFU growth of Cryptococcus spp) in combination with oral flucytosine (100mg/kg) for 7 days and then fluconazole 1200mg once daily for the next 11 days. By day 7, she was symptom free and quantitative cerebrospinal fluid culture was negative for Cryptococcus spp. She was discharged on day 9. At 10 weeks (day +40) and 18 weeks (day +72), she was well and adherent to her antiretroviral therapy and on maintenance phase of cryptococcal meningitis on fluconazole at a dose of 400mg once daily.Conclusion: This report alerts clinicians managing patients with HIV-associated cryptococcal meningitis to four uncommon clinical scenarios; first, the possibility of negative serum and cerebrospinal fluid CrAg lateral flow assay results in the context of low cerebrospinal fluid fungal burden in a symptomatic patient. Second, possible occurrence of cryptococcal meningitis in a patient with high CD4 T-cell lymphocyte counts. Third, an early seroconversion of cryptococcal antigenaemia following effective fluconazole therapy. Fourth, an early symptomatic relapse of cryptococcal meningitis albeit negative serum CrAg.Keywords: cryptococcal antigen test, cryptococcal meningitis, amphotericin B, fluconazole, flucytosine, India ink